Effects of hemodialysis on blood fatty acids. Issue 2 (24th January 2020) - Gollasch, Benjamin; Dogan, Inci; Rothe, Michael; Gollasch, Maik; Luft, Friedrich C.
Abstract: Omega‐3 (n‐3) fatty acids have beneficial cardiovascular effects, perhaps also in chronic kidney disease (CKD) patients. A low omega‐3 index is an independent cardiovascular risk factor in end‐stage renal disease (ESRD) dialysis patients. However, the plasma measurements invariably ignore circulating blood cells, including the preponderant erythrocytes (RBCs). We measured fatty acids (HPLC‐MS lipidomics) in all components of the circulating blood, since RBC n‐3 fatty acid status has been linked to cardiovascular disease and mortality. We studied 15 healthy persons and 15 CKD patients undergoing regular hemodialysis treatments. While total fatty acid levels differed significantly in RBCs from healthy controls and CKD patients, the hemodialysis treatment had no effect on plasma or RBC fatty acid levels. No changes occurred in the percentage of eicosapentaenoic acid (C20:5 n‐3, EPA) and docosahexaenoic acid (C22:6 n‐3; DHA) (omega‐3 quotient) in RBC membrane fatty acids. Nonetheless, hemodialysis treatments increased plasma levels of various total fatty acids, namely C12:0, C14:0, C16:0, C20:2 n‐6, C20:4 n‐6, and C22:6 n‐3 (DHA), while plasma levels of free fatty acids were unchanged. These data suggest that despite significant changes in fatty acids signatures between healthy persons and CKD patients, hemodialysis does not alter RBC n‐3 fatty acid status, including the omega‐3 quotient. The dialysis treatment per se does not appear to be responsible for a lower omega‐3 index in CKD patients. Abstract : Omega‐3 (n‐3) fatty acids have beneficial cardiovascular effects, perhaps also in chronic kidney disease (CKD) patients. We measured fatty acids (HPLC‐MS lipidomics) in all components of the circulating blood. Our data demonstrate significant changes in fatty acid signatures between healthy persons and CKD patients. However, dialysis treatment per se does not appear to be responsible for a lower omega‐3 index in CKD patients.